2016
DOI: 10.1177/1533034616672806
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the IL-6 rs1800795 Polymorphism and the Risk of Cervical Cancer: A Meta-Analysis of 1210 Cases and 1525 Controls

Abstract: Cervical cancer is the second most common cancer and the third leading cause of cancer-related death among females in less developed countries. Studies have shown that the single-nucleotide polymorphisms of interleukin 6 might be associated with cervical cancer risk. A total of 710 articles from EMBASE, EBSCO, Web of science, PubMed, Springer link, and Chinese National Knowledge Infrastructure databases were reviewed in our study. A meta-analysis on the associations between interleukin 6 rs1800795 polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Several recent meta-analysis have focused on the association between IL-6 promoter polymorphisms and cancer risk. Two meta-analysis showed that rs1800795 polymorphism increased the risk of prostate cancer and cervical cancer [ 108 , 109 ]. Though, the result same with ours, it still exist some problems.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent meta-analysis have focused on the association between IL-6 promoter polymorphisms and cancer risk. Two meta-analysis showed that rs1800795 polymorphism increased the risk of prostate cancer and cervical cancer [ 108 , 109 ]. Though, the result same with ours, it still exist some problems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Pu et al [ 26 ] found that cervical cancer risks were significantly higher in carriers of C allele of rs1800795 polymorphism than those with GG genotype. By now, only one meta-analysis by Liu et al [ 30 ] was conducted to explore the association between IL-6 -174G>C and cervical cancer risk. This meta-analysis was updated to July 2015 with five publications included (1210 cases and 1525 controls).…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies suggested that IL-12B rs3212227 and IL-6 rs1800795 polymorphisms are associated with an increased risk of cervical cancer. However, two recent meta-analyses were performed to evaluate IL-12B rs3212227 and IL-6 rs1800795 polymorphisms with cervical cancer risk and their results indicated that no significant association was found among all ethnicities (Chang et al, 2015;Liu et al, 2017;Pu et al, 2016;Zheng et al, 2017). Therefore, controversy and inconformity still remained about IL-12B rs3212227 and IL-6 rs1800795 polymorphisms and most of studies recruited a limited sample capacity, which is insufficient to get a firm conclusion about the associations of these polymorphisms with development of cervical cancer.…”
Section: Association Of Il-12b Rs3212227 and Il-6 Rs1800795mentioning
confidence: 99%